2018
DOI: 10.2196/mhealth.8873
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of mHealth Interventions: Systematic Review of Systematic Reviews

Abstract: BackgroundMobile phone usage has been rapidly increasing worldwide. mHealth could efficiently deliver high-quality health care, but the evidence supporting its current effectiveness is still mixed.ObjectiveWe performed a systematic review of systematic reviews to assess the impact or effectiveness of mobile health (mHealth) interventions in different health conditions and in the processes of health care service delivery.MethodsWe used a common search strategy of five major scientific databases, restricting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
622
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 895 publications
(695 citation statements)
references
References 38 publications
15
622
0
7
Order By: Relevance
“…Considering the chronic nature of multiple sclerosis and importance of self-management in its control (17), the emerging trend observed in developing m-health apps seems to be in a right direction. Since m-health tools have the potential to better facilitate adherence of patients with chronic diseases to treatment and management regimens (29-31), the observed increase in the number of such apps for self-management of multiple sclerosis can lead to more involvement of the patients in managing their conditions. In addition, considering the fact that the attitude of people with MS is positive on the use of Smartphone technology for health care purposes (32, 33), this can be promising for the success of MS self-management apps.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the chronic nature of multiple sclerosis and importance of self-management in its control (17), the emerging trend observed in developing m-health apps seems to be in a right direction. Since m-health tools have the potential to better facilitate adherence of patients with chronic diseases to treatment and management regimens (29-31), the observed increase in the number of such apps for self-management of multiple sclerosis can lead to more involvement of the patients in managing their conditions. In addition, considering the fact that the attitude of people with MS is positive on the use of Smartphone technology for health care purposes (32, 33), this can be promising for the success of MS self-management apps.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing availability of mHealth interventions for health behavior change (Marcolino et al, ), approaches to guide the revision of existing interventions are needed. During the review of literature, no approaches were identified that outline consideration for mHealth interventions targeted for use by children and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile health, or mHealth, is defined as “medical and public health practice supported by mobile devices, such as mobile phones, patient monitoring devices, personal digital assistants, and other wireless devices” (World Health Organization, , p. 6). mHealth may overcome barriers to care and improve resource delivery in difficult‐to‐reach populations; thus, mHealth is a useful avenue for delivering health behavior change interventions (Marcolino et al, ; Thirumurthy & Lester, ). Furthermore, mHealth interventions have been shown to improve symptom outcomes, quality of life, healthcare utilization, and medication adherence in populations with chronic conditions (Marcolino et al, ) and have the potential for monitoring and implementing disease management plans in chronic conditions (Nilsen et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the chronic nature of multiple sclerosis and importance of self-management in its control [17], the emerging trend observed in developing m-health apps seems to be in a right direction. Since m-health tools have the potential to better facilitate adherence of patients with chronic diseases to treatment and management regimens [29][30][31], the observed increase in the number of such apps for self-management of multiple sclerosis can lead to more involvement of the patients in managing their conditions. In addition, considering the fact that the attitude of people with MS is positive on the use of Smartphone technology for health care purposes [32,33], this can be promising for the success of MS self-management apps.…”
Section: Discussionmentioning
confidence: 99%